Intermittent breath holding during moderate bicycle exercise provokes consistent changes in muscle oxygenation and greater blood lactate response - Kume, D.; Akahoshi, S.; Song, J.; Yamagata, T.; Wakimoto, T.; Nagao, M.; Matsueda, S.; Nagao, N. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: This study examined the effect of intermittent breath holding (IBH) on physiological response, including oxygenation in working muscle, to moderate-intensity exercise. Methods: Thirteen men performed bicycle exercise for 5 min at 65% of peak oxygen uptake with normal breathing (NB) and with IBH. Muscle oxygenation, concentration changes of oxyhemoglobin (deltaOxy-Hb), deoxyhemoglobin (deltaDeoxy-Hb) and total hemoglobin (deltaTotal-Hb), in the right vastus lateralis were continuously monitored using near-infrared spectroscopy (NIRS). Finger capillary blood samples were taken after exercise for analyzing blood lactate concentration (BLa). Results: NIRS parameters showed acute changes to each BH episode in the IBH condition (Total-Hb and deltaOxy-Hb decreased, deltaDeoxy-Hb increased). Accordingly, in the IBH condition, deltaOxy-Hb was lower (PConclusion: These results suggest that IBH during moderate-intensity exercise provokes consistent changes in muscle oxygenation, leading to lower tissue oxygenation. Our data also indicate that exercise with IBH induces higher BLa.